Simulation of Tyre Stiffness of Marine Pneumatic Friction Clutch - Wang Zhonghou; Wang Bingqing; Liu Xinrong; Zhang Yi; Fu Shunjun (Jixie chuandong)
In the dynamics simulation of the pneumatic tyre on marine clutch,the establishment of nonlinear model of pneumatic tyre is the hardest part in the simulation. Based on the platform of Abaqus,the finite element model is established with the consideration of geometric nonlinearity,material nonlinearity and boundary conditions nonlinearity,meanwhile the inflation process of tyre is simulated. Through the data interactive technology between Abaqus and ADAMS,the modal neutral file generated from Abaqus is imported into ADAMS to complete the dynamics model. The axial rigidity,radial rigidity and torsional rigidity of the pneumatic tyre are test in Abaqus and ADAMS. Finally,the analysis results and the actual results is compared to prove the correctness of the simulation. This research can lay the foundation for the research of the dynamic simulation of engagement and vibration noise of the marine pneumatic friction clutch.